School Vouchers: A Survey of the Economics Literature - Epple, Dennis; Romano, Richard E.; Urquiola, Miguel (Journal of Economic Literature, 2017)
We review the theoretical, computational, and empirical research on school vouchers, with a focus on the latter. Our assessment is that the evidence to date is not sufficient to warrant recommending that vouchers be adopted on a widespread basis; however, multiple positive findings support continued exploration. Specifically, the empirical research on small-scale programs does not suggest that awarding students a voucher is a systematically reliable way to improve educational outcomes, and some detrimental effects have been found. Nevertheless, in some settings, or for some subgroups or outcomes, vouchers can have a substantial positive effect on those who use them. Studies of large-scale voucher programs find student sorting as a result of their implementation, although of varying magnitude. Evidence on both small-scale and large-scale programs suggests that competition induced by vouchers leads public schools to improve. Moreover, research is making progress on understanding how vouchers may be designed to limit adverse effects from sorting, while preserving positive effects related to competition. Finally, our sense is that work originating in a single case (e.g., a given country) or in a single research approach (e.g., experimental designs) will not provide a full understanding of voucher effects; fairly wide-ranging empirical and theoretical work will be necessary to make progress. (JEL H52, H75, I21, I22, I28, O15)